The impact of a massive transfusion protocol (1:1:1) on major hepatic injuries: Does it increase abdominal wall closure rates? - Ball, Chad G. (Canadian Medical Association, 2013)
BACKGROUND: Massive transfusion protocols (MTPs) using high plasma and platelet ratios for exsanguinating trauma patients are increasingly popular. Major liver injuries often require massive resuscitations and immediate hemorrhage control. Current published literature describes outcomes among patients with mixed patterns of injury. We sought to identify the effects of an MTP on patients with major liver trauma. METHODS: Patients with grade 3, 4 or 5 liver injuries who required a massive blood component transfusion were analyzed. We compared patients with high plasma:red blood cell:platelet ratio (1:1:1) transfusions (2007–2009) with patients injured before the creation of an institutional MTP (2005–2007). RESULTS: Among 60 patients with major hepatic injuries, 35 (58%) underwent resuscitation after the implementation of an MTP. Patient and injury characteristics were similar between cohorts. Implementation of the MTP significantly improved plasma: red blood cell:platelet ratios and decreased crystalloid fluid resuscitation (p = 0.026). Rapid improvement in early acidosis and coagulopathy was superior with an MTP (p = 0.009). More patients in the MTP group also underwent primary abdominal fascial closure during their hospital stay (p = 0.021). This was most evident with grade 4 injuries (89% vs. 14%). The mean time to fascial closure was 4.2 days. The overall survival rate for all major liver injuries was not affected by an MTP (p = 0.61). CONCLUSION: The implementation of a formal MTP using high plasma and platelet ratios resulted in a substantial increase in abdominal wall approximation. This occurred concurrently to a decrease in the delivered volume of crystalloid fluid.